Seeking Moderation Amid Religious Extremism and Political Turmoil: A Case Study of Afghanistan - Samiullah Adel; Mahmood Rahimi; Abid Ullah (SYAMIL: Journal of Islamic Education, 2024)
This study investigates the interplay of Islamic ideology, violence, and political strategies in contemporary Afghanistan, examining domestic and foreign influences. This study applies library resources to explore the delicate relationships between Afghan Islamic philosophy, politics, and warfare by utilizing a thematic analysis framework. By closely analyzing the historical development of Islamic philosophy, politics, and violence in Afghanistan, as well as the impact of foreign stakeholders, the study aims to offer a thorough understanding of this interconnected web of complexities. Employing thematic analysis to dissect Islamic thoughts in Afghanistan, stressing the diversity of viewpoints and the vital role of external stakeholders. This research will shed light on the complex interplay of terrorism relationships among terrorism, politics, and conflict resolution, highlighting the dire need for Wasatiyya (moderation). By bridging historical viewpoints with contemporary ground realities, the study will offer an understanding of Afghanistan’s socio-economic and political complexities. This article significantly contributes to the academic discourse and directs future research into the complex political realities within the region.